Terapi Rendam Kaki Menggunakan Air Hangat Pada Pasien Lansia Hipertensi dengan Masalah Keperawatan Nyeri Akut - Cardo, Alex; Rimbawati, Yazika; Parmin, Selamat; Afdhal, Fitri Afdhal (JURNAL KESEHATAN TERAPAN, 2026)
Hypertension is one of the most common health problems experienced by the elderly and is often accompanied by acute pain complaints. Non-pharmacological management such as warm foot soak therapy can be an alternative to lower blood pressure as well as reduce pain. This study aimed to implement nursing care with the intervention of warm foot soak therapy in elderly patients with hypertension experiencing acute pain. The research method used was a case study design involving two elderly hypertensive patients at Bhayangkara Mohamad Hasan Hospital, Palembang, in 2025. The intervention was carried out by soaking the patients’ feet in warm water at a temperature of 37–40 °C for 15–30 minutes, once a day for three consecutive days. Data were collected through observations of blood pressure and pain scale using an assessment sheet. The results showed a decrease in blood pressure in both patients, from 180/80 mmHg to 150/80 mmHg and from 170/90 mmHg to 140/80 mmHg. In addition, the pain scale decreased significantly, from 5 to 1 and from 4 to 2. In conclusion, warm foot soak therapy is effective as a non-pharmacological nursing intervention to help reduce blood pressure and relieve pain in elderly patients with hypertension.